Evaluación de la retención de humedad en un queso duro no madurado, a partir de leche entera con adición de harina de chocho y carragenina. - Villarroel Basantes, Shirley Dayana (2022)
The main objective of this research is to evaluate the moisture retention in an unripened hard cheese, from whole milk with the addition of lupine flour and carrageenan, which influence the percentage increase in moisture in cheese production. Taking advantage of the protein value present in lupine flour without shell with a percentage of 58.17% protein where unripened hard cheeses were made, from different concentrations of lupine flour and carrageenan, resulting in cheeses with different levels moisture. Through an InfoStat statistical package with a randomized complete block design (DBCA), in a factorial arrangement A*B+1, the best treatment was determined based on the percentage of moisture that corresponds to treatment nine (a3b3) with a formulation 3% lupine flour and 0.05% carrageenan. Physical analyzes were performed at the best treatment: density 1.04g/ml, titratable acidity 0.31g/kg, pH 6.1; also chemical analysis: total moisture 53.57%, dry matter 46.43%, protein 21.61%, fiber 1.07%, fat 19.58%, ash 6.20%, and; microbiological analysis: total coliforms 10UFC/g, absence of escherichia coli and salmonella, sthaphylococcus aureus 5UFC, molds 10UFC, yeasts 10UFC/g Through a sensory evaluation carried out with the best treatment, the organoleptic characteristics were determined, such as: color, odor , flavor, texture and acceptability, where high scores between 4 and 5 were obtained. Finally, this research generates positive impacts, both technical, social, environmental and above all economic, associated with water retention performance; The project can contribute with the proposal of new dairy products with a high protein level, as well as link small producers of milk, lupine and dairy industries and all consumers who require new products with added value.